PEMANFAATAN POTENSI LOKAL MELALUI INOVASI PANGAN CENDOL LELE DURIAN SEBAGAI USAHA PRODUKTIF - Dalman, Dalman; Fakhrurozi, Moh; Warsiyah, Warsiyah; Saputeri, Noorikha Pandayahesti (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
Pekon Mulyorejo, located in Pringsewu Regency, Lampung, has great potential in the development of local food-based culinary businesses. Most of the people in this region make a living as farmers and catfish cultivators, but their production is still sold in raw form with relatively low economic value. This community service program aims to increase the added value of local products through food processing innovation by combining cendol, catfish, and durian into unique and high-selling value culinary products. The methods used in this program include production training, technical assistance, and marketing development. The program was carried out for 6 months involving 25 participants consisting of PKK women and MSME actors in Pekon Mulyorejo. The results of the program showed a significant improvement in the participants' food processing skills, the creation of an innovative product "Cendol Lele Durian" which has received a positive response from the local market, as well as an increase in the average income of participants by 35%. The sustainability of the program is guaranteed through the formation of business groups and continuous assistance in production and marketing aspects.